2012
DOI: 10.1152/ajpgi.00040.2012
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of SKCa and TREK1 channels in purinergic and nitrergic neuromuscular transmission in the rat colon

Abstract: Purinergic and nitrergic neurotransmission predominantly mediate inhibitory neuromuscular transmission in the rat colon. We studied the sensitivity of both purinergic and nitrergic pathways to spadin, a TWIK-related potassium channel 1 (TREK1) inhibitor, apamin, a small-conductance calcium-activated potassium channel blocker and 1H-[1,2,4]oxadiazolo[4,3-α]quinoxalin-1-one (ODQ), a specific inhibitor of soluble guanylate cyclase. TREK1 expression was detected by RT-PCR in the rat colon. Patch-clamp experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Interestingly, contrary to its antinociceptive effect, morphineinduced reduction in gastroinstestinal tract function was unchanged in TREK-1 KO mice; all parameters tested were identical in both genotypes. This result is consistent with the recent observations that the nitrergic-induced inhibition of neuromuscular transmission in the gastrointestinal tract, an important factor in morphine-induced constipation 47 , does not involve TREK-1 channels 48 . It demonstrates that analgesia and constipation, two usual effects of opioids, do not involve the same mechanisms downstream from mOR.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, contrary to its antinociceptive effect, morphineinduced reduction in gastroinstestinal tract function was unchanged in TREK-1 KO mice; all parameters tested were identical in both genotypes. This result is consistent with the recent observations that the nitrergic-induced inhibition of neuromuscular transmission in the gastrointestinal tract, an important factor in morphine-induced constipation 47 , does not involve TREK-1 channels 48 . It demonstrates that analgesia and constipation, two usual effects of opioids, do not involve the same mechanisms downstream from mOR.…”
Section: Discussionsupporting
confidence: 93%
“…, and ICC-GCKO (13 cells from 6 animals). In the global GCKO, a nitrergic IJP was not measurable; on the contrary, the purinergic IJP was followed by a slight depolarization (10 cells from 5 animals Studies investigating the downstream targets of cGMP revealed the involvement of cGMP-dependent protein kinase I (PKG), but the identity of further downstream mediators is uncertain (14,26,32). In a recent publication, Klein et al (24) proposed PKG to be the exclusive mediator of the nitrergic IJP in colonic ICC, based on an apparently abolished nitrergic hyperpolarization in ICC-specific PKG KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the activation of apamin-sensitive SK channels by low-frequency field stimulation has been associated with the relaxation of isolated mouse stomach [23], andpurinergic stimulation of mouse ileum [24] and colon [8] triggers the opening of apamin-sensitive SK channels, which also participate in the relaxation of mouse distal colon induced by nitric oxide treatment [25]. In our study, after the CCh-induced maximal contraction of colonic circular muscle, administration of apamin led to the contraction of the muscle again quickly, which confirmed that the activation of apamin-sensitive SK channels might inhibit colon contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The SK family in mammals includes SK1, SK2, and SK3. In addition, SK2 and SK3 are expressed in the colon, and apamin-sensitive SK channels underlie the relaxing effect of purinergic stimulation on the colon and might also play a role on the nitrergic relaxation pathway [8]. …”
Section: Introductionmentioning
confidence: 99%